Reliability of "in-season" fitness assessments in youth elite soccer players: A working model for practitioners and coaches - Enright, K.; Morton, J.; Iga, J.; Lothian, D.; Roberts, S.; Drust, B. (Science and Medicine in Football, 2018)
Purpose: To assess the reliability of a battery of field tests when performed around habitual training during one micro-cycle of the "in-season" period in youth elite soccer players. Methods: n = 19 English Premier League academy players (mean ± SD: age, 18.3 ± 0.2 years; stature, 1.80 ± 0.05 m; body mass, 76.5 ± 7.5 kg; O2 max, 62.3 ± 4.38 ml/kg/min; sum of 8 skinfolds, 64.8 ± 17.4 mm) performed; "1RM half-back squat (HBS)", "vertical jump" (VJ), "Yo-Yo IR2", "5, 10 & 20 m, sprint", change of direction "CoD test", "repeated sprint ability" assessments around their habitual "in-season" training and match-play on two occasions. Intraclass correlations (ICC), typical errors, coefficient of variations (CV), effect sizes and the smallest difference needed to be considered real (MD) were calculated for each test. Results: Most assessments demonstrated good levels of variability (CV; 0.3-4.3%, ICC; 0.83-0.99). To witness an "almost certain beneficial change" (i.e., >MD), changes of approximately 5% are needed for RSAbest, RSAmean, 10m and 20m sprint, "CoD" and 1RM HBS. Whereas, changes of 9-11.5% for CMJ, 5m sprint and Yo-Yo IR2 are needed. Conclusions: The present training and testing "model" is reliable and could be used when evaluating the fitness of highly trained youth elite soccer players during the "in-season" period.